2007
DOI: 10.1016/j.jpeds.2007.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Pubertal Status at Age 11 and Lower Physical Activity in Adolescent Girls

Abstract: Girls experiencing early pubertal maturation at age 11 reported lower subsequent physical activity at age 13 than their later maturing peers. Pubertal maturation, in particular early maturation relative to peers, may lead to declines in physical activity among adolescent girls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
75
2
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 47 publications
5
75
2
2
Order By: Relevance
“…However, if this decline remains even if controlled by body fat, the cause can be attributed to external factors and not to biological variables. Evidence shows a decrease in physical activity levels with advancing sexual maturation stages (26,27) . This suggests that the reduced physical activity level observed in this phase of life (27) can be a factor that contributes to the low cardiorespiratory fitness levels found.…”
Section: Discussionmentioning
confidence: 99%
“…However, if this decline remains even if controlled by body fat, the cause can be attributed to external factors and not to biological variables. Evidence shows a decrease in physical activity levels with advancing sexual maturation stages (26,27) . This suggests that the reduced physical activity level observed in this phase of life (27) can be a factor that contributes to the low cardiorespiratory fitness levels found.…”
Section: Discussionmentioning
confidence: 99%
“…In contradiction, a longitudinal study of 2247 adolescent girls reported that early maturing girls in grades 7 and 8 participated in more minutes of self-reported vigorous PA than late maturing girls; however, this association was not seen among girls in grades 9 through 11 (29). Baker et al (2) showed that early maturing girls (assessed via a combination of estradiol, breast development, and mother's report on pubertal development using the pubertal development scale at age 11) participated in less accelerometer measured PA at age 13 when compared with late maturing girls. Likewise, a study by Riddoch et al (19) showed that parental reported pubic hair and breast development was inversely related to PA among 2933 11-yr-old girls.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 Prior research found that advanced pubertal girls had significantly lower self-reported PA and accumulated fewer minutes of moderate-to-vigorous and vigorous PA and accelerometer counts per day at age 13 years than girls that physically mature later. 38 This may be particularly 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 important for girls who are overweight or obese, as they are more likely to begin puberty earlier than their healthy-weight peers. 39 However, we found virtually no differences in obesity prevalence between most common sports and non-athletes/participants-in-other-activities in girls.…”
Section: Discussionmentioning
confidence: 99%